Mobilidade urbana: análise da legislação do município de Araguaína - Santos, Maycon Afonso Fragoso dos (Universidade Federal do Tocantins, 2020)
This study aims to analyze the legislation of the municipality that affect the system of urban mobility of the same. In this sense, the objective of this article was to analyze the Organic Law of the municipality of Araguaína-TO to identify the articles that directly or indirectly deal with urban mobility and urban transport, considering that the municipality does not have a mobility plan, the specific objective Is to make a link between these articles in order to analyze their relationships with the city's experienced landscape. It was used in the research the deductive method, as to its nature the research is of the applied type in which the knowledge is used in the practice in order to solve certain concrete problems. As to the objectives of the research is characterized as descriptive exploratory, these procedures made it possible to understand the current scenario of urban mobility and urban transportation, built from the municipal legislations.